Al-Doped chitosan nonwoven in a novel adsorption reactor with a cylindrical sleeve for dye removal: performance and mechanism of action. Issue 112 (22nd November 2016) - Li, Su; Yang, Jing; Rashid, Sadia; Shen, Chensi; Liu, Jianshe
Abstract : To overcome the inconvenience of solid/liquid separation of powdered adsorbents, a novel adsorption reactor with a cylinder sleeve was designed to match the textile-pattern of chitosan nonwoven for the sake of easy separation and simple operation. Abstract : In order to overcome the inconvenience of solid/liquid separation of powdered adsorbents, a novel adsorption reactor with a cylindrical sleeve was designed to match the textile-pattern of chitosan nonwoven for the sake of easy separation, simple operation and high efficiency. Meanwhile, Al-doped chitosan nonwoven was prepared to enhance the adsorption ability of chitosan nonwoven through the chelation interaction between dyes and metal centers of the Al-doped chitosan nonwoven. In this system, the adsorption of C. I. Acid Red 73 into Al-doped chitosan nonwoven could maintain high efficiency in a wide pH range from 3 to 10, with a high maximum adsorption capacity of 260.03 mg g −1 . Additionally, the studies of reusability, pH sensitivity, the effect of the coexisting ions and the adsorption of other organic dyes indicated that the Al-doped chitosan nonwoven fixed in as a cylindrical sleeve within a reactor was technically feasible, highly efficient, and implies a potential of practical application for dyeing effluent treatment.